ANALYSIS OF THE INFLUENCE AND RELATIONSHIP OF THE EFFECT OF PERFORMANCE FACTORS ON THE QUALITY PERFORMANCE OF SUPERVISORY CONSULTANTS - Setyo, Mayogo; Muhammadun, Haris; Oetomo, Wateno (Transpublika Publisher, 2022)
Roads are the main means for the community to mobilize to carry out their respective activities. With the vital function of roads, it is important for roads to carry out regular road maintenance. Road maintenance carried out must also be of good quality so that road functions can continue to be used properly and have a durable condition. This study aims to analyze the influence and relationship of Influence factors on the Quality Performance of Supervisory Consultants. The research population was 75 Road Maintenance Supervisory Consultants with a total sample of the entire population. The research data collection technique used a questionnaire. The analytical technique chosen to analyze the data and test the hypothesis in this study used Partial Least Square (PLS). The results indicate that Human Resources and Work Execution Methods have no significant effect on the Quality Performance of Supervisory Consultants. Meanwhile, understanding of technical, environmental and managerial specifications has a significant effect on the Quality Performance of the Supervisory Consultant.